Identifikasi Mikoriza Vesikular Arbuskular pada Rhizosfer Kopi Arabika (Coffea arabica L.) dan Kopi Robusta (Coffea robusta L.) dan Perbanyakannya dengan Media Zeolit - PUTU AYU MEITA YUDIA DEWI; MADE SRITAMIN; I KETUT SUADA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Vesicular Arbuscular Mycorrhizae Identification of Arabica Coffee(coffea arabica L.) and Robusta Coffee (Coffea robusta L.) Rhizosphere andIts Spore Multiplication in Zeolite Media.The high demand of coffee in the world led the farmers to improve coffee productivity by using inorganic fertilizers. Considering potential problems that may occured due to inorganic fertilizer use, aplication of biological fertilizer which one of them is containing Vesicular Arbuscular Mycorrhizae (VAM) could be expected to assist the growth of Arabica coffee and Robusta coffee plants in more naturally manner. This study aimed to determine the types mycorrhizal of rhizosphere coffee plants and determine the effectiveness of zeolite media and corn symbiont plant in propagation of VAM. The study began in April to August 2015. Spore isolation was done by conducting wet sieving method. Roots colonization percentages were calculated by root staining method and spores multiplication through trapping culture method. The results showed that VAM spores found in the rhizosphere arabica coffee plants are two genera VAM Acaulospora and Glomus, whereas in robusta coffee plant found three genera Acaulospora, Glomus, and Gigaspora. Mycorrhizal structures found in the rhizosphere of Arabica and Robusta coffee plants were arbuscular, vesicles, hyphae and inner spores. Corn symbionts plant and zeolite media were good combination for the propagation of VAM spores.